PENGARUH BERBAGAI KOMPOSISI MEDIA TANAM DAN PEMBERIAN PUPUK NPK MUTIARA (16:16:16) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum l.) - Yanita Febriani Harianja; Heti Herastuti; Tuti Setyaningrum (Program Studi Agroteknologi INSTIPER, 2022)
Shallots are one of the leading horticultural commodities that have been cultivated by farmers for a long time. Constraints in the cultivation of shallots in Indonesia are environmental conditions such as soil types. This study aims to determine the effect of the type of planting medium and the application of NPK fertilizer on the growth and yield of shallot (Allium ascalonicum L.). This research is conducted at Caping Merapi which is located at Jl. Raya Tajem KM 2.5, Wedomartani, Ngemplak, Sleman, D.I.Yogyakarta from November 2021 to January 2022. The research design used was a split-plot design using 2 factors: the dose of NPK fertilizer and the composition of the growing media. The main plot is NPK fertilizer and the sub-plot is the type of planting media. The data obtained are analyzed using variance (Anova). The results of the variance showed a significant effect, then continued with the Duncan test (DMRT) with a 5% level. The results show that there is no interaction between the treatment of the type of planting media and the dose of NPK fertilizer on the growth and yield of shallots. The effect of giving the type of peat soil planting media was better on plant height and number of leaves. The application of 15 grams/plant was better for the number of leaves, number of tillers, fresh weight of leaves, fresh weight of tubers, and number of tubers. Keywords: Shallots, NPK, Regosol Soil, Peat